Relationship of Soluble Klotho and Early Stage of Diabetic Nephropathy: A Systematic Review and Meta-Analysis - Xin, Caihong; Sun, Xin; Li, Zheng; Gao, Tianshu (Frontiers in Endocrinology, 2022)
Background: Diabetic nephropathy (DN) is a chronic microvascular complication caused by long-term hyperglycemia in patients with diabetes and an important cause of end-stage renal disease. Although some studies have shown that soluble Klotho(sKlotho) levels of patients with DN are lower than those without DN, in the early stage of patients with DN with normal renal function and albuminuria, the change in sKlothois still controversial. Aim: This meta-analysis was conducted to statistically evaluate sKlotho levels in patients with DN. Methods: We searched the following electronic databases: Web of Science, Embase, PubMed, Google Scholar, and China National Knowledge Infrastructure (CNKI). The following search terms were used for the title or abstract: “diabetic kidney disease,” “diabetic nephropathy,” OR “DN” in combination with “Klotho.” The meta-analysis results were presented as standardized mean differences (SMDs) with corresponding 95% confidence intervals (CIs). Results: Fourteen articles were included in the meta-analysis. In our meta-analysis, we found that the sKlotho level in patients with DN was significantly lower than that in patients without DN (SMD: -1.52, 95% CI [-2.24, -0.80]), and it was also significantly lower in the early stage of DN (SMD: -1.65, 95% CI [-2.60, -0.70]). Conclusions: This systematic review was the first to evaluate the relationship between sKlotho levels and DN. The sKlotho level was significantly lower in the early stages of DN, indicating that sKlotho might be a new biomarker of DN in the future.